Kidney functions and electrolyte disturbance among Iraqi patients with bladder cancer - Ahmed, Noor I.; Ali, Rawaa H.; Ismail, Mohammed B. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Bladder cancer is among the most prevalent cancers worldwide, with 549,393 new cases reported in 2018. Approximately 3% of all new cancer diagnoses and 2.1% of all cancer deaths are due to urinary bladder cancer.Objectives: This study aims to explore the efficiency of renal system functions as indicated by renal function tests and electrolyte levels among bladder cancer patients.Methods: All patients in this case-control study were recruited from Ghazi Al-Hariri Hospital for surgical specialties in Baghdad during the period from December 2021 to June 2022. A total of 100 individuals were enrolled in this study and divided into two groups. The first group included 50 patients with an age range of (16-79) years. All patients were first diagnosed and investigated with a bladder mass by transurethral resection of bladder tumor (TURBT) and sent to the histopathological examination for biopsy of bladder lesion. The second group included 50 healthy individuals.Results: The results of the present study showed that all renal function tests and serum electrolyte levels were in the upper limit or within the normal range, although some of these levels were significantly different between patients and controls.Conclusion: All renal function tests were within the upper limits of the normal range as most of the bladder tumors were low-grade small-sized masses.